Creation of the Person-Centered Wellness Home in Older Adults. Issue 1 (22nd January 2020) - Mielenz, Thelma J; Tracy, Melissa; Jia, Haomiao; Durbin, Laura L; Allegrante, John P; Arniella, Guedy; Sorensen, Julie A
Abstract: Background and Objectives: Extending the Patient-Centered Medical Home (PCMH) model into the community may address the poor linkage between medical clinics and underserved communities. Our first of three objectives was to determine if peer leaders and wellness coaches can be the relationship center of wellness care. We evaluated the Self-management Resource Center Small Group Programs (SMRCSGP), plus wellness coaching, as a booster intervention in older adults with chronic diseases. Second, we evaluated the role of personal health records (PHR) prototype as the linkage between the clinic and community. Using input from these two objectives, we lay the groundwork for the Person-centered Wellness Home (PCWH). Research Design and Methods: Participants enrolled from five South Bronx New York City Housing Authority communities. We conducted a pragmatic, randomized controlled trial using two arms ( n = 121): (1) SMRCSGP and (2) SMRCSGP plus wellness coaching initiated as a booster after SMRCSGP completion. Adjusted individual growth models compared the slope differences for outcomes. We conducted a social networking analysis on the ties between wellness coaches and participants. PCMH-certified physicians completed in-depth interviews on the PHR prototype. An adaptation from the consensus-workshop model summarized the priority PCWH items. Results: There was an improvement in self-reported physical functioning (2.0 T-score units higher, p = .03) by the wellness coaching group, but the groups did not differ on physical activity. From the social networking analysis, connections were stable over time with wellness-coaches and participants. The Consensus Conference identified eight major components of the PCWH. Discussion and Implications: Wellness coaching post-SMRCSGP was a booster to physical function, an upstream outcome for physical activity. During the Consensus-Conference, community-based prevention marketing and personal navigators for connecting to a PCMH emerged as novel components. This supports future work in training community health workers as peer leaders to provide evidence-based programs and other PCWH components.